Meta-analysis of vascular endothelial growth factor variations in amyotrophic lateral sclerosis: increased susceptibility in male carriers of the −2578AA genotype. Issue 12 (15th April 2008) - Lambrechts, D; Poesen, K; Fernández-Santiago, R; Al-Chalabi, A; Del Bo, R; Van Vught, P W J; Khan, S; Marklund, S L; Brockington, A; van Marion, I; Anneser, J; Shaw, C; et al.
Abstract : Background: Targeted delivery of the angiogenic factor, vascular endothelial growth factor (VEGF), to motor neurons prolongs survival in rodent models of amyotrophic lateral sclerosis (ALS), while mice expressing reduced VEGF concentrations develop motor neuron degeneration reminiscent of ALS, raising the question whether VEGF contributes to the pathogenesis of ALS. An initial association study reported that VEGF haplotypes conferred increased susceptibility to ALS in humans, but later studies challenged this initial finding. Methods and findings: A meta-analysis was undertaken to critically reappraise whether any of the three common VEGF gene variations (−2578C/A, −1154G/A and −634G/C) increase the risk of ALS. Over 7000 subjects from eight European and three American populations were included in the analysis. Pooled odds ratios were calculated using fixed-effects and random-effects models, and four potential sources of heterogeneity (location of disease onset, gender, age at disease onset and disease duration) were assessed. After correction, none of the genotypes or haplotypes was significantly associated with ALS. Subgroup analysis by gender revealed, however, that the −2578AA genotype, which lowers VEGF expression, increased the risk of ALS in males (OR = 1.46 males vs females; 95% CI = 1.19 to 1.80; p = 7.8 10E-5), even after correction for publication bias and multiple testing. Conclusions: This meta-analysis does not support the original conclusion that VEGF haplotypes increase the risk of ALS in humans, but the significant association of the low-VEGF −2578AA genotype with increased susceptibility to ALS in males reappraises the link between reduced VEGF concentrations and ALS, as originally revealed by the fortuitous mouse genetic studies.